The effect of social screening on bond mutual fund performance - Henke, Hans-Martin (Journal of Banking & Finance, 2016)
This study measures the financial impact of screening for environmental, social and governance criteria on corporate bond portfolios. Specifically, the risk-adjusted financial performance of 103 socially responsible bond funds in the US and the Eurozone is compared with a matched sample of conventional funds. During the period 2001–2014, socially responsible bond funds outperform by one-half of one percent annually. An evaluation of fund holdings and a performance-attribution analysis suggest that this outperformance is directly related to the mitigation of ESG risks, which is achieved by the exclusion of corporate bond issuers with poor corporate social responsibility activities. A separation of crisis and non-crisis periods further indicates that the outperformance is especially likely to occur during recessions or bear market periods. We confirm this crisis-related return effect from a sample of socially screened bond indices. Moreover, our results are robust to alternative definitions of sustainability, survivorship bias, fund characteristics and stable in the US and Eurozone sub-samples.